Livin' la vida loca - Martin, Ricky; Sony Music Entertainment (New York : Sony Music Entertainment, 1999)
Contains three versions of the single.
CD 1 : Album version / (4:03) -- Spanish version / (4:03) -- Spanglish version / (4:03).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Popular music; Songs, English